Development of Learning Tools Based on Realistic Mathematical Approaches to Improve Mathematical Problem Solving Ability of Students in Class V SD Angkasa 2 Lanud Soewondo Medan - Widda Syafira Abd. Wahab; Sahat Saragih; Siman Siman (BIRCU, 2020)
This research is motivated by learning tools that do not meet the effectiveness criteria in SD Angkasa 2 Lanud Soewondo Medan. This study aims to describe: 1) the effectiveness of learning tools based on realistic mathematical approaches in improving students' mathematical problem solving abilities; 2) increasing students' mathematical problem solving abilities by using realistic mathematics-based learning tools; 3) the process of student answers in solving problems mathematical problem solving abilities. This study uses a 4-D development model. The subjects in this study were all class V SD Angkasa 2 Lanud Soewondo Medan, with a total of 41 students. The objects in this study are learning tools in the form of lesson plans, textbooks, student activity sheets, and tests of mathematical problem solving abilities. The results showed that: 1) learning devices based on realistic mathematical approaches effectively improve mathematical problem-solving abilities, effectiveness in terms of: a) the percentage of students' mastery learning classically which reached 95.24%; b) achievement of the ideal percentage of student activity time for each category; and c) the average value of the teacher's ability to manage learning is 4.8, including the good category; 2) improvement of students' mathematical problem solving abilities, the average value of achieving mathematical problem solving abilities in the first trial of 45.00 increased to 95.24 in the second trial; 3) the process of students' answers in completing the problem solving ability test questions in try II is better than try I. Then it is recommended that teachers be able to use learning tools based on realistic mathematical approaches as alternative learning.